2015
DOI: 10.1063/1.4907193
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weak excitatory synapses on chaotic transients in a diffusively coupled Morris-Lecar neuronal network

Abstract: Spatiotemporal chaos collapses to either a rest state or a propagating pulse solution in a ring network of diffusively coupled, excitable Morris-Lecar neurons. Weak excitatory synapses can increase the Lyapunov exponent, expedite the collapse, and promote the collapse to the rest state rather than the pulse state. A single traveling pulse solution may no longer be asymptotic for certain combinations of network topology and (weak) coupling strengths, and initiate spatiotemporal chaos. Multiple pulses can cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Such a configuration has, to our knowledge, not yet been demonstrated, and it extends the usual notion of a chaotic saddle in spatially extended systems, in the sense that it provides a mechanism for switchings between more than two distinct space-time patterns. Transient spatiotemporal chaos studied in other systems governed by a chaotic saddle usually exhibits one type of dynamics [87,88] or at most two alternative patterns as observed in a neuronal network [86] or in a modified complex Ginzburg-Landau equation on two spatial subdomains [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a configuration has, to our knowledge, not yet been demonstrated, and it extends the usual notion of a chaotic saddle in spatially extended systems, in the sense that it provides a mechanism for switchings between more than two distinct space-time patterns. Transient spatiotemporal chaos studied in other systems governed by a chaotic saddle usually exhibits one type of dynamics [87,88] or at most two alternative patterns as observed in a neuronal network [86] or in a modified complex Ginzburg-Landau equation on two spatial subdomains [41].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these examples, however, have in common that the chaotic saddle is characterized by one type of spatiotemporal dynamics. Recently it has been reported that in transient spatiotemporal chaos the alternation between two different space-time patterns either on the whole spatial domain [86] or on two subdomains [41] can be observed. By contrast, the chaotic saddle identified here has a more complicated structure since it contains three different space-time patterns and an irregular switching between them mediated by channel-like structures in phase space.…”
Section: Manifolds and Phase Spacementioning
confidence: 99%
“…There are many studies of spatiotemporal patterns in systems of excitable cells (Fujii and Tsuda 2004 ; Hartle and Wackerbauer 2017 ; Keplinger and Wackerbauer 2014 ; Lafranceschina and Wackerbauer 2014 ; Mondal et al. 2018 ; Calim et al.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been published on spatiotemporal patterns in networks of excitable cells [28,35,49,54,65,12]. Tsyganov et.…”
Section: Introductionmentioning
confidence: 99%